Technology Literacy of Undergraduate Students: A Survey in Universitas Muhammadiyah Malang - Kusumastuti, Frida; Erianti, Ribut Wahyu; Yumitro, Gonda; Roziqin, Ali; Dintarini, Mayang; Salahudin, Salahudin; Arrozy, Ahmad; Wicaksono, Agung P.N (BRILIANT: Jurnal Riset dan Konseptual, 2022)
The development of information technology and globalization has impacted the learning process of higher education in Indonesia. This study aims to describe the level of technological literacy of students at the University of Muhammadiyah Malang in supporting the Independent Learning Campus (MBKM) policy of universities in Indonesia. This article uses a survey approach through a google form distributed purposively to students using a quantitative method. The survey uses a Likert scale adopted by the PISA standard, UNESCO. The results of this study indicate that the level of technological literacy for students who have participated in the Merdeka Learn Campus Merdeka (MBKM) is high. Furthermore, the survey shows that information literacy and digital literacy have good scores from the four elements of technological literacy: information literacy, digital literacy, and internet literacy. Two faculties have high technological literacy, namely the Faculty of Health Sciences and Teacher Training and Education. The implication of this research is to provide input information for higher education managers to make decisions on the development of the Independent Learning Campus Merdeka (MBKM) in higher education